A dinorcassane-type diterpene and a steroidal saponin from Distemonanthus benthamianus Baill. (Caesalpiniaceae). (April 2022) - Kepdieu Tchebou, Robert V.; Eckhardt, Paul; Kemkuignou, Blondelle Matio; Tchuenguem, Roland; Fouedjou, Romuald Tematio; Ponou, Beaudelaire Kemvoufo; Dzoyem, Jean Paul; Teponno, Rémy Bertrand; Barboni, Luciano; Opatz, Till; Tapondjou, Léon Azefack
Abstract: As part of our search for new bioactive compounds from medicinal plants growing in Cameroon, a previously unreported dinorcassane-type diterpenoid trivially named distemonanthin (1 ) and a new steroidal saponin, stigmasta-5, 22-dien-3- O-β -D -glucopyranosyl-(1→3)- O-β -D -glucopyranoside (2 ) together with ten known compounds were isolated from the ethyl acetate and n -butanol soluble fractions of the methanol extract from the stem barks of Distemonanthus benthamianus . Their structures were established using 1D and 2D NMR spectroscopy, mass spectrometry and by comparison with spectroscopic data reported in the literature. The extract, fractions and some isolated compounds were screened for their antimicrobial properties and a significant inhibition was observed only for the n -butanol fraction against Candida albicans and Candida glabrata with MICs values of 32 and 64 µg/mL, respectively. Graphical Abstract: ga1 Highlights: The phytochemical investigation of Distemonanthus benthamianus was achieved. Twelve compounds including to new secondary metabolites were isolated. Their structures were elucidated by spectroscopic and chemical methods. The extracts and some compounds were screened for their antimicrobial activity. A weak activity was observed for epirobinetinidol against two microbial strains.